Activation of Transient Receptor Potential Melastatin Subtype 8 Attenuates Cold‐Induced Hypertension Through Ameliorating Vascular Mitochondrial Dysfunction. Issue 8 (August 2017) - Xiong, Shiqiang; Wang, Bin; Lin, Shaoyang; Zhang, Hexuan; Li, Yingsha; Wei, Xing; Cui, Yuanting; Wei, Xiao; Lu, Zongshi; Gao, Peng; Li, Li; Zhao, Zhigang; et al.
Abstract : Background: Environmental cold‐induced hypertension is common, but how to treat cold‐induced hypertension remains an obstacle. Transient receptor potential melastatin subtype 8 (TRPM8) is a mild cold‐sensing nonselective cation channel that is activated by menthol. Little is known about the effect of TRPM8 activation by menthol on mitochondrial Ca 2+ homeostasis and the vascular function in cold‐induced hypertension. Methods and Results: Primary vascular smooth muscle cells from wild‐type or Trpm8 −/− mice were cultured. In vitro, we confirmed that sarcoplasmic reticulum–resident TRPM8 participated in the regulation of cellular and mitochondrial Ca 2+ homeostasis in the vascular smooth muscle cells. TRPM8 activation by menthol antagonized angiotensin II induced mitochondrial respiratory dysfunction and excess reactive oxygen species generation by preserving pyruvate dehydrogenase activity, which hindered reactive oxygen species–triggered Ca 2+ influx and the activation of RhoA/Rho kinase pathway. In vivo, long‐term noxious cold stimulation dramatically increased vasoconstriction and blood pressure. The activation of TRPM8 by dietary menthol inhibited vascular reactive oxygen species generation, vasoconstriction, and lowered blood pressure through attenuating excessive mitochondrial reactive oxygen species mediated the activation of RhoA/Rho kinase in a TRPM8‐dependent manner. These effects of menthol were further validated in angiotensin II–induced hypertensive mice. Conclusions: Long‐term dietary menthol treatment targeting and preserving mitochondrial function may represent a nonpharmaceutical measure for environmental noxious cold–induced hypertension.